2014
DOI: 10.1016/j.addbeh.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of internet addiction and its association with stressful life events and psychological symptoms among adolescent internet users

Abstract: Internet addiction (IA) among adolescents is a serious public health problem around the world. However, there have been few studies that examine the association between IA and stressful life events and psychological symptoms among Chinese adolescent internet users. We examined the association between IA and stressful life events and psychological symptoms among a random sample of school students who were internet users (N=755) in Wuhan, China. Internet addiction, stressful life events, coping style and psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
124
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(151 citation statements)
references
References 27 publications
20
124
2
5
Order By: Relevance
“…3,10 Several studies have reported higher prevalence of internet addiction viz Ghamari et al and Tang et al, 10.8% and 6.0% respectively. 11,12 The findings of this study suggest that there was a significant difference between gender and internet addiction which corroborates with the previous studies stating that addiction were more common in males than in females. 9,11,13 however, the Internet usage levels of females have increased in recent years.…”
Section: Discussionsupporting
confidence: 82%
“…3,10 Several studies have reported higher prevalence of internet addiction viz Ghamari et al and Tang et al, 10.8% and 6.0% respectively. 11,12 The findings of this study suggest that there was a significant difference between gender and internet addiction which corroborates with the previous studies stating that addiction were more common in males than in females. 9,11,13 however, the Internet usage levels of females have increased in recent years.…”
Section: Discussionsupporting
confidence: 82%
“…Este é um resultado controverso, uma vez que existem autores que demostram que o género masculino está associado a dependência de Internet e outros negam a diferença entre géneros. [33][34][35][36][37] O uso de redes sociais e jogos online foi associado a dependência por outros autores, 38 contudo os nossos resultados demonstraram apenas associação positiva entre dependência de Internet e uso de RS. Este resultado refuta a ideia inicialmente aceite que a dependência de Internet não seria mais do que dependência de jogos online.…”
Section: % (N) % (N)unclassified
“…Life stress from interpersonal relationships and school are correlated positively with Internet Addiction in adolescents, and there is a positive correlation with anxiety [6]. Problematic Internet Use was associated with sleep problems including subjective insomnia and poor sleep quality too [7].…”
Section: Introductionmentioning
confidence: 87%